2019
DOI: 10.1111/ans.15358
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in patients with malignant melanoma: analysis of post‐operative complications

Abstract: Background: This study investigates the incidence of post-operative complications and risk factors of sentinel lymph node biopsy (SLNB) in melanoma patients. Methods: A retrospective cohort study was conducted at a single cancer institution on 408 consecutive SLNBs. Results: Fifty-five post-operative complications occurred in 39 (9.5%) patients and included: wound infection in 24 (5.9%), seroma and lymphorrhea in 15 (3.7%), wound dehiscence in seven (1.7%), lymphocele in six (1.5%) and others in three (0.7%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The standard protocol for SLNB involves preoperative lymphoscintigraphy using an injection of radiocolloid, followed by intraoperative LN mapping using blue dye. According to reports in the literature, blue dye and radiocolloid particles can pass through the first echelon LNs due to their small size (20), leading to more extensive dissection and increased complications (27). Blue dye is often avoided in facial melanoma for esthetic and surgical reasons (28).…”
Section: Discussionmentioning
confidence: 99%
“…The standard protocol for SLNB involves preoperative lymphoscintigraphy using an injection of radiocolloid, followed by intraoperative LN mapping using blue dye. According to reports in the literature, blue dye and radiocolloid particles can pass through the first echelon LNs due to their small size (20), leading to more extensive dissection and increased complications (27). Blue dye is often avoided in facial melanoma for esthetic and surgical reasons (28).…”
Section: Discussionmentioning
confidence: 99%
“…Predictors included age, body mass index (BMI), diabetes, smoking status, number of previously undergone surgeries in the groin, ASA classification, delayed DSNB, type of DSNB protocol (1 or 2 day), administration of prophylactic antibiotics before surgery, number of removed LNs (histopathology) and presence of SN metastasis. Pre-selection of variables was based on possible clinical relevance and/or previously described associations with the occurrence of postoperative complications after inguinal lymphadenectomy and DSNB in other malignancies [5,[18][19][20][21][22]. It is more likely that the risk of postoperative complications is similar within one patient and as several patients underwent multiple DSNB procedures (multiple measurements), the generalised linear mixed model included the 'patients' variable as a random effect with random intercept to correct for the non-independence of the data.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The 13.7% complication rate in our study is comparable to other papers with rates ranging from 9.5% to 25%; Moody et al . conducted a systematic review in 2016 identifying an average complication rate of 11.3% across 21 studies 17,27,32,40–42 . Consistently across all research, the most frequently observed complications after a SLNB were wound infection and seroma formation.…”
Section: Discussionmentioning
confidence: 86%
“…Lymphoedema: Excess accumulation of lymphatic fluid in a limb due to lymphatic system insufficiency after surgery, resulting in localized swelling 16 Bleeding/haematoma: Unexpected blood loss during the post‐operative period and/or a localized collection of blood at the surgical site 17 Graft failure: Unsuccessful adherence of the graft to the wound site and/or failure of revascularisation 18 …”
Section: Methodsmentioning
confidence: 99%